GUARANTEE OF HALAL PRODUCTS SELF DECLARE CONCEPT OF MICRO AND SMALL ENTERPRISES ECONOMICS - Saputera, Ikhwan; Jamalie, Zulfa; Azhari, Fathurrahman (Proceeding International Seminar of Islamic Studies, 2024)
Implementation of the self-declare concept in halal product guarantees, especially in the context of micro and small enterprise (UMK) economic actors, which is focused on understanding how the self-declare process can provide convenience and certainty for UMK in obtaining halal certification . The implementation of self-declaration is in line with changes to the halal certification system in Indonesia, this mechanism ensures that the self-declare policy only applies to UMK that meet certain criteria, in line with the government's efforts to encourage the growth of the UMK sector and increase the competitiveness of halal products. It is hoped that self-declaration can create certainty and guarantee of halal products for Muslim consumers, as well as support the growth of the halal industry at national and international levels. ‎